2019
DOI: 10.1177/0269216319885818
|View full text |Cite
|
Sign up to set email alerts
|

Core outcome domains of pediatric palliative care for children with severe neurological impairment and their families: A qualitative interview study

Abstract: Background: The interest in outcome measurement in pediatric palliative care is rising. To date, the majority of studies investigating relevant outcomes of pediatric palliative care focus on children with cancer. Insight is lacking, however, about relevant outcome domains for children with severe neurological impairment and their families. Aim: The aim of this study was to identify meaningful outcome domains of pediatric palliative care for children with severe neurological impairment and their families. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 30 publications
0
28
0
2
Order By: Relevance
“…Non-invasive capnography potentially detects respiratory depression in children and adults earlier than pulse oximetry [ 46 , 47 , 48 ]. However, an additional nasal cannula/face mask may not be suitable for the palliative care setting, where normalcy is a recurrent wish voiced by families [ 49 ]. Thus, monitoring respiratory rate changes probably provides the greatest predictability of imminent respiratory depression and failure [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive capnography potentially detects respiratory depression in children and adults earlier than pulse oximetry [ 46 , 47 , 48 ]. However, an additional nasal cannula/face mask may not be suitable for the palliative care setting, where normalcy is a recurrent wish voiced by families [ 49 ]. Thus, monitoring respiratory rate changes probably provides the greatest predictability of imminent respiratory depression and failure [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…and M.R. The wording of the items was inspired by the language used by parents and professional caregivers in the interviews conducted by Ribbers et al 17 A total of 67 items were generated.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, both the original and the translated version of the African C-POS may not be applicable to children with congenital and neurological disorders, who constitute the largest patient group in developed countries for children younger than 16 years. 8 Based on a previous study that identified relevant aspects of pediatric palliative care for children with severe neurological impairment and their families, 17 this study aims to develop and validate a multidimensional familycentered outcome measure for this population. A parent and professional caregiver version will be created.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with severe neurological impairment and their families have substantial palliative care needs and yet are the subject of very little research. In this issue, Reuther and colleagues 8 make a notable contribution by identifying six core domains of paediatric palliative care for these families, including symptom control, as commonly seen in other populations.…”
mentioning
confidence: 99%